Rupture of IIeum Due to Blunt Trauma Abdomen - Arif, Muhammad; Mannan, Pervez (Journal of Postgraduate Medical Institute, 2011)
An Isolated complete tear of a portion of ileum with its mesentry due to blunt trauma leading to acute abdomen is described.